Dementia care in European countries, from the perspective of people with dementia and their caregivers. (27th November 2014) - Karlsson, Staffan; Bleijlevens, Michel; Roe, Brenda; Saks, Kai; Martin, Maria Soto; Stephan, Astrid; Suhonen, Riita; Zabalegui, Adelaida; Hallberg, Ingalill R.; the RightTimeCarePlace Consortium
Abstract Aim To investigate persons with dementia and their informal caregivers' views of inter‐sectoral information, communication and collaboration throughout the trajectory of dementia care, in eight European countries. Background Living with dementia and being next of kin to a person with dementia means having to live through stages that have different characteristics, needs, challenges and requirements. Design Qualitative research. Focus groups were conducted in England, Estonia, Finland, France, Germany, The Netherlands, Spain and Sweden. Methods Persons with dementia and their informal caregivers (N = 137) participated in focus group interviews during 2011. Content analysis generated a tentative model of information, communication and collaboration for people with dementia and their caregivers, which was then tested. Results The core finding was that information, communication and collaboration were to be focused on the persons with dementia and the informal caregivers. Entering into the trajectory of the disease and its consequences was addressed as an important point of departure. The relation to professional care required establishing a trusting relationship, tailor‐made intervention and a single person or organization to contact. Professional knowledge and commitment, variation in service and care adapted to needs were important. Conclusion As focus of care is on the person with dementia and their informal caregivers, a dyadic approach seems most suitable for dementia care. A trusting relationship and a specific person or organization to contact seem to be indicators of best practice, as does adaptation to the needs of the person with dementia and their informal caregiver.